Konsep Diri Anak-anak Pengguna Aktif Media Sosial - Laila Hayati (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2018)
It is undeniable that the recent development of internet technology has given tremendous benefits. It can facilitate human beings to communicate each other. The advance use of internet i.e. social media has been forming the digital society into unlimited access of information and interaction irrespective with the gender, education, status, ethnicity and else via Instagram, Facebook, Tik Tok and others. This paper aims to unsderstand how children as the social media users have the self-concept in their environment. The study used qualitative approach through observation and in-depth interview with thw respondents. The result showed that the children concept themselves as an adult. It was due to the exposure of the social media’s content they used.